Medicare Payment Penalties and Safety Net Hospital Profitability: Minimal Impact on These Vulnerable Hospitals. (8th February 2018) - Bazzoli, Gloria J.; Thompson, Michael P.; Waters, Teresa M.
Abstract : Objective: To examine relationships between penalties assessed by Medicare's Hospital Readmission Reduction Program and Value‐Based Purchasing Program and hospital financial condition. Data Sources/Study Setting: Centers for Medicare and Medicaid Services, American Hospital Association, and Area Health Resource File data for 4, 824 hospital‐year observations. Study Design: Bivariate and multivariate analysis of pooled cross‐sectional data. Principal Findings: Safety net hospitals have significantly higher HRRP/VBP penalties, but, unlike nonsafety net hospitals, increases in their penalty rate did not significantly affect their total margins. Conclusions: Safety net hospitals appear to rely on nonpatient care revenues to offset higher penalties for the years studied. While reassuring, these funding streams are volatile and may not be able to compensate for cumulative losses over time.